Iran's Persian Gulf policy : from Khomeini to Khatami - Marschall, Christin, 1966- (RoutledgeCurzon, 2003)
This book examines the foreign policy of the Islamic Republic of Iran towards the Persian Gulf states from 1979 to 1998.